Design, Optimization and Experimental Evaluation of a F-shaped Multiband Metamaterial Antenna - Diego C. Corrêa; Ursula C. Resende; Fabiano S. Bicalho; Yan S. Gonçalves (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract A F-shapedprinted dipole antenna, designed to operate simultaneously at 1.8 GHz, 2.45 GHz and 5.8 GHz is proposed in this work. The main challenge of the project is to find the antenna optimal geometry so that its gain has a higher value in the three operating frequencies in order to be efficiently applied it in the energy harvesting and wireless communication systems. To achieve the proposed operating condition, reduce the antenna return loss and enhance its bandwidth and gain a metamaterial surface was incorporated into its structure. All simulations and optimizations were performed using the Computer Simulation Technology software by employing the Finite Difference Time Domain technique for the electromagnetic equations evaluation. The antenna and metamaterial geometrical dimensions were optimized by using the Genetic Algorithm technique. Numerical and experimental evaluations were performed for the antenna with and without the metamaterial structure incorporated. The results obtained demonstrate the appropriately designed metamaterial ability to improve the antennas performance, increasing their bandwidth and gain and decreasing the return loss value.